Adverse reactions induced by MDT/WHO (Rifampicin+Clofazimine+Dapsone) and ROM (Rifampicin+Ofloxacin+Minocycline) regimens used in the treatment of leprosy: a cohort study in a National Reference Center in Brazil - Celestino, Isadora Costa; Antunes, Douglas Eulalio; Santos, Diogo Fernandes; Gimenes, Victor Lemos; de Souza, Fabiane Mian; Goulart, Isabela Maria Bernardes (Frontiers in Pharmacology, 2024)
Background: Recommended standard treatment for leprosy is multidrugtherapy (MDT/WHO), consisting Rifampicin+Dapsone+Clofazimine. Other medications are recommended in cases of resistance, adverse reactions and intolerances, including ROM regimen, Rifampicin+Ofloxacin +Minocycline. Therefore, pharmacovigilance is an important tool in understanding these adverse drug reactions (ADRs), supporting pharmacotherapy management and medication safety. This study seeks to evaluate ADRs comparing two therapeutic regimens, MDT and ROM, used in treatment of patients with leprosy, analyzing prognostic factors regarding risk and safety.Methods: A retrospective cohort study was performed by assessing medical records of 433 patients diagnosed with leprosy from 2010 to 2021 at a National Reference Center in Brazil. They were subject to 24 months or more of treatment with MDT or ROM regimens. ADR assessments were analyzed by two experienced researchers, who included clinical and laboratory variables, correlating them with temporality, severity and the causality criteria of Naranjo and WHO. The findings observed an average of 1.3 reactions/patient. Out of individuals experiencing reactions, 67.0% (69/103) were utilizing MDT/MB, while 33.0% (34/103) were using ROM. The median time for ADR of 79 days for MDT and 179 days for ROM. In first reaction, Dapsone was the most frequently involved medication; the most affected system was hematopoietic. As compared to Clofazimine, results indicated that use of Dapsone was associated with 7% increased risk of ADR occurrence (HR: 1.07; p=0.866). Additionally, Rifampicin was linked to 31% increased risk of ADRs (HR: 1.31; p=0.602); and Ofloxacin showed 35% elevated risk (HR: 1.35; p=0.653). Conversely, results for Minocycline indicated 44% reduction in the risk of ADRs (HR: 0.56; p=0.527), although statistical significance was not reached. The use of MDT conferred 2.51 times higher risk of developing ADRs in comparison to ROM.The comparison between MDT and ROM revealed that MDT caused more ADRs, and these reactions were more severe, indicating less safety for patients. Dapsone was the most common medication causing ADRs, followed by Rifampicin. The combination with Clofazimine was associated with an additional risk of ADRs, warranting further studies to confirm this hypothesis. Given the high magnitude of ADRs, healthcare teams need to monitor patients undergoing leprosy treatment with focus on pharmacovigilance.